On secular stagnation and low interest rates: Demography matters - Giuseppe Ferrero; Marco Gross; Stefano Neri (European Central Bank (ECB), 2017)
Nominal and real interest rates in advanced economies have been decreasing since the mid-1980s and reached historical low levels in the aftermath of the global financial crisis. Understanding why interest rates have fallen is essential for both monetary policy and financial stability. This paper focuses on one of the factors that have been put forward in the literature within the secular stagnation view: adverse demographic developments. The main conclusion that we draw from our empirical, panel equation system-based assessment is that these developments have exerted downward pressures on real short- and long-term interest rates in the euro area over the past decade. Moreover, building on the European Commission projections for dependency ratios until 2025, we illustrate that the foreseen structural change in terms of age structure of the population may dampen economic growth and continue exerting downward pressure on real interest rates also in the future.
Keywords: C32; E52; J11; 330; secular stagnation; demographic developments; real interest rates; monetary policy